REPRESENTASI BODY SHAMING DALAM FILM ‘YOLO’ - Rohmadani; Irwanto; Panji Suratriadi (Tamilis Synex: Multidimensional Collaboration, 2025)
Film is a type of work of art that has extraordinary appeal to people throughout the world. Apart from being entertainment, films also function to convey stories, messages and emotions to the audience. This research examines the film YOLO (2024) which raises the issue of body shaming, especially towards individuals with larger body sizes. Body shaming is a social phenomenon that often gives rise to stigma and discrimination and creates a deep negative impact on the mental and emotional health of the individual who is the victim. This research aims to analyze scenes that contain symbolic meaning that reflect negative attitudes and behavior towards the individual, which often causes discomfort and decreased self-confidence in the victim. Using qualitative methods and using a critical paradigm with John Fiske's semiotic analysis, this research involves rare – systematic steps such as film observation, identification of body shaming issues through coding data scenes, and data reduction to focus on related aspects. The research results showed that body shaming behavior depicted in the film caused feelings of discomfort and low self-confidence, thus affecting the victim's ability to socialize and interact with other people around them. This research emphasizes the importance of rejecting such behavior and encouraging inclusive attitudes towards body diversity.